Understanding the predisposing risk factors of young suicide - Wardhan, Rashmi; Mudgal, Padmshree (International Journal of Research in Medical Sciences, 2020)
Suicide is an unfortunate multifactorial problem impacting families and communities. Many young lives are lost every year due to suicide. There is an urgent need to understand the multifactorial risk factor mechanisms providing vulnerability to suicidal behavior for early detection of impending incidents, monitoring, and prevention. This review aims to give an insight into the various biochemical and genetic markers along with the associated socio-economic factors and mental disorders which contribute to increased suicide risk. The role of different neurotransmitter-associated pathways such as serotonin, gamma aminobutyric acid (GABA), and norepinephrine pathway, and pathways involving the hypothalamic-pituitary-adrenal (HPA) axis, lipid metabolism, and neuroinflammation in suicide ideation and risk have been explored. Understanding of these predisposing factors and associated pathways could help identify the risk and lead to the development of drugs/ treatment to prevent suicides.